PENERAPAN POLA PENGEMBANGAN MANAJEMEN KARIR KARYAWAN PT.BANK BENGKULU - Ratnawili Ratnawili; Nunung Rahayu (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
This study aims do determine the application of the petten of planning and career management of employees of PT Bank Bengkulu this study used descrivtive method Based on the conclusion from the presentation of the data obtained career planning at PT. Bank Bengkulu has not been going well because from the individual dimension it has not maximized efforts for career advancement. Wether its efforts in indentifying career goals, the steps taken in career achievement, and the is no systematic and well organized career plan arrangement. Circumstances like this will make it difficultfor themselves as employee sin determining their career progress. PT. Bank Bengkulu basically alighns the organization need for human. Resources and the availablity of existing human resources. Career management at PT. Bank Bengkulu has been running weel. To direct career development to benefit the organization and employees, the personal department often holds training and development programs forÃ‚Â  employees, Thus employees must further improve their performance and work discipline to be considered in employee career development at PT. Bank Bengkulu.